Impact of leadership styles toward employee performance during WFH arrangement the case of Eastwest Bank and Philippine National Bank (PNB) in Tacloban City, Leyte - Achazo, Ronneth Jean S.; Maderazo, Cheina N.; Nuez, Daryl Aye A.; Perez, Patricia Mae C.
This study investigates the impact of leadership style toward employee performance during WFH arrangements in the case of Eastwest and PNB in Tacloban City, Leyte. Several studies regarding the impact of leadership styles on workers' performance have been carried out but rather concentrate on face-to-face working arrangements. Hence, this study examines and identifies the direct influence of transformational and transactional leadership styles and work-from-home setup on employee performance within the participating banks amid the COVID-19 pandemic, and to distinguish the suitable leadership style managers should adopt during WFH arrangement that boosts employee job performance. The researchers adopted a mixed-method case study approach and used a survey questionnaire and a semi-structured interview to attain relevant data. Furthermore, non-probability convenience sampling was. utilized for determining the sample size, along with the application of complete enumeration from which 2 managers and 10 employees were the respondents of the said study. Finally. frequency tables, descriptive Statistics, and thematic Analysis were used in analyzing and presenting the data gathered. The findings of the study revealed that both managers from East West and PNB exhibit a mix of traits from both transactional and transformational leadership styles but practice a more transformational leadership style. It also revealed the characteristics being applied during the WFH arrangement namely, people management, being proactive, goal-oriented, and a flexible leader or manager. Additionally, a framework is developed which shows how each leadership style's unique characteristics affect employee performance. The study concluded that it is imperative that managers use the appropriate leadership style that would effectively influence and motivate their employees to perform well, as supported by the model of Hogan and Kaiser (2005) shows that since leaders and their leadership styles affect employees' behaviors, and employees' behaviors affect organizational performance, then leadership styles affect organizational performance. In the case of East West and PNB branches in Justice Romualdez Street Tacloban City, the transformational leadership style is the suitable leadership style during the WFH arrangement as it is effective in improving employee performance amidst the pandemic.